2019
DOI: 10.3390/ma12233908
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Segmented Nanowires: A High Tech Bright Future

Abstract: In the last couple of decades, there has been a lot of progress in the synthesis methods of nano-structural materials, but still the field has a large number of puzzles to solve. Metal nanowires (NWs) and their alloys represent a sub category of the 1-D nano-materials and there is a large effort to study the microstructural, physical and chemical properties to use them for further industrial applications. Due to technical limitations of single component NWs, the hetero-structured materials gained attention rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 205 publications
(250 reference statements)
0
33
0
Order By: Relevance
“…Progress in this field is well reported in other articles and is thus not further discussed herein. [ 217 ]…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
“…Progress in this field is well reported in other articles and is thus not further discussed herein. [ 217 ]…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
“…Electrodeposition is versatile and simple technique to synthesize the 1-D magnetic nano materials. [22][23][24][25][26][27][28][29] Fe and Mn materials are chosen based on the idea that, the nanometer Fe has very large magnetic susceptibility, and paramagnetic Mn has many unpaid electrons in their outer most shell, by combining the two materials as 1-D multilayer structure, the biocompatibility and high sensitivity can be obtain to provide the required MR images.…”
Section: Prepared Fe 3 O 4 @Gd 2 O 3 Core-shellmentioning
confidence: 99%
“…To address the above stated problems, one‐dimensional Fe/Mn multilayered NWs, and single component Fe and Mn NWs was prepared by electrodeposition in 30 nm diameter anodic aluminum oxide (AAO) template. Electrodeposition is versatile and simple technique to synthesize the 1‐D magnetic nano materials 22‐29 . Fe and Mn materials are chosen based on the idea that, the nanometer Fe has very large magnetic susceptibility, and paramagnetic Mn has many unpaid electrons in their outer most shell, by combining the two materials as 1‐D multilayer structure, the biocompatibility and high sensitivity can be obtain to provide the required MR images.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, complementary studies have reported the magnetic behavior of multi-segmented NWs with tuned lengths of the non-magnetic layer, e.g., Co/Cu [ 27 , 33 ], Ni/Cu [ 21 , 23 , 34 ], CoFe/Au [ 29 ], CoFe/Cu [ 35 ] FeCoCu/Cu [ 36 ], FeCo/Cu [ 37 ], and CoFeB/Cu [ 32 ] nanostructures. These works have demonstrated that the magnetic behavior of the multilayered nanoarchitectures can be selectively tuned according to the required applications [ 20 , 38 , 39 , 40 ]. However, to employ such structures in biomedical applications, and since Co and Ni possess high toxicity levels, the need to fabricate completely biocompatible segmented NWs has arisen.…”
Section: Introductionmentioning
confidence: 99%